Future people a moderate consequentialist account of our obligations to future generations - Mulgan, Tim.; Oxford eBooks (Oxford : Clarendon, 2006)
The author develops a new theory of our obligations to future generations, based on a rule-consequentialist account of the morality of individual reproduction. His aim is to produce a coherent, intuitively plausible moral theory which can be extended to cover future people.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Duty; Consequentialism (Ethics); Electronic books